2009
DOI: 10.12968/bjon.2009.18.7.41652
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the development of calculating skills in nurses

Abstract: This article discusses a well-known model in mathematical problem solving developed by Polya (1957) and suggests that this could be a beneficial framework to support the development of medication calculation skills. The model outlines four stages to problem solving: understanding the problem, devising a plan, carrying out the plan and examining the solution. These four stages are discussed in relation to the teaching and assessing of medication skills, drawing on literature from nursing, mathematics education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…drug‐dose calculation skills in the first class should be considered in the following classes). In agreement with this aim, studies have emphasized that drug‐dose calculation skills should be reviewed before clinical practice and emphasized during clinical practice (McMullan et al ., ; Wright, ). Additionally, nurse educators need to support, guide, and counsel students (Jukes & Gilchrist, ; McMullan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…drug‐dose calculation skills in the first class should be considered in the following classes). In agreement with this aim, studies have emphasized that drug‐dose calculation skills should be reviewed before clinical practice and emphasized during clinical practice (McMullan et al ., ; Wright, ). Additionally, nurse educators need to support, guide, and counsel students (Jukes & Gilchrist, ; McMullan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization recommends the use of simulation‐based education to improve the security of patients (WHO, ). Many studies have demonstrated that simulation‐based education that includes real physician orders helped to positively develop dose calculation skills (Weeks, Clochesy, Hutton, & Moseley, ; Wright, ). Fidelity is an important concept in simulation‐based education.…”
Section: Introductionmentioning
confidence: 99%
“…Calculation skills have long been recognised to be a part of the overall problem (Jukes and Gilchrist, 2006) and models have been presented and discussed proposing different strategies for teaching the arithmetic necessary. Some studies have emphasised the importance of increasing the student's understanding of logical processes underpinning pharmacokinetics and pharmacodynamics while others have emphasised the clinical context related to drug administration (Warburton and Kahn, 2007;Wright, 2009;Weeks et al, 2013;Fleming et al, 2014;Young et al, 2014). It has been recognised however that many students are still hanging on to anxiety that was related to problems encountered during their primary education (Wright, 2006) even after they have demonstrated competency by passing a drug calculation exam.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two of the four Cs involve basic mathematical skills. Another mathematical problem-solving model is the four-step model of Poyla, 22 which has the following stages: (i) understand the problem, (ii) devise a plan, (iii) execute the plan, and (iv) examine the solution. This model stresses the importance of understanding the mathematical problem before attempting to derive its solutions.…”
Section: Strategies For Teaching Medication Calculationmentioning
confidence: 99%